Protective role of vacuum vs. atmospheric frying on PUFA balance and lipid oxidation. (August 2016) - Albertos, I.; Martin-Diana, A.B.; Jaime, I.; Diez, A.M.; Rico, D.
Abstract: The effect of vacuum frying processing on proximate composition, fatty acid profile, oxidative status and sensorial properties of fish patties, was evaluated as compared with conventional (atmospheric) frying. Vacuum frying procedure was carried out at 80 mmHg (water boiling point: 42 °C) and oil temperature (107 °C) determined to obtain an equivalent thermal driving force (Δ65 °C) of that of the atmospheric frying conditions used (165 °C). Frying times of 2, 4, 6, 8 and 10 min were investigated. Vacuum frying significantly prevented degradation of EPA (Eicosapentaenoic acid) and DHA (Docosahexaenoic acid), reducing the polyene index and maintaining a lower ω6/ω3 fatty acid ratio in samples, while no significant differences with conventional frying in total oil content were observed. The use of vacuum also reduced formation of peroxides and carbonyl derivatives. Tocopherol levels decreased in all samples regardless of the frying conditions used, although vacuum-fried samples maintained higher tocopherol levels after processing. These samples also showed higher lightness and lower a* and b* values, which can be associated to lower non-enzymatic browning levels. These results support the applicability of vacuum frying technology for fish patties, since it prevents colour changes, improves juiciness and reduces oxidation when compared to conventionally (atmospheric) fried counterparts. Industrial relevance: Consumers are increasingly aware of the link between food and health, maintaining a high demand for healthy products. In this regard, consumption of fatty fish, with healthy properties widely known, is lower than recommended by health authorities, especially in children. Novel processing technologies focused on increasing the appealing of products based on fatty fish can help in ameliorating this deficient consumption. Vacuum frying is a promising way of obtaining attractive products, due to some product modification after the deep-fat frying process, and yet retaining natural colour, juiciness and healthy properties to a high extent. Vacuum frying allows reducing ω3 fatty acids and tocopherol degradation, differentiating fish products so obtained, which can be launched into the market and benefit from this technology. Compared to conventional frying, the results are better nutritional and sensory properties in a final product. Highlights: Vacuum frying reduced degradation of ω3 PUFA compared with conventional frying. The use of vacuum reduced formation of peroxides and carbonyl derivatives. Vacuum frying maintained better tocopherol levels. Vacuum frying reduced colour changes and improved juiciness.